Oncle Jazz - Lim, Esther Mu Hui (Nanyang Technological University, 2021)
Oncle Jazz is a conceptual visual album for the Canadian Indie band Men I Trust and is named after their 2019 album Oncle Jazz. More than a completed project, Oncle Jazz is also an open-ended inquiry on designing animated loops, motion for sound, and reviewing systems for sustainable growth in the author’s own art practice. This thesis will examine the project through the lens of experimental animation, which echoes many characteristics in this project.